Analysis of the Heat Transfer Performance of Nanofluids in Micro-Cylinder Groups - Lina Wafaa Belhadj Senini; Mustpaha Boussoufi; Amina Sabeur (East European Journal of Physics, 2023)
The objective of this study is to investigate, through numerical simulations, the flow and heat transfer characteristics of Al2O3, Cu, TiO2, and SiC water-based nanofluids flowing over micro-cylinder groups arranged in an inline configuration. The simulations were carried out under laminar flow conditions, and the analysis considered seven different low values of the Reynolds number, with a constant volume fraction of 2%. The aim of this investigation was to determine how nanofluids, i.e., suspensions of nanoparticles in water as the base fluid, can affect the pressure drop and heat transfer performance in micro-cylinder groups. To accomplish this, the finite volume method was employed to evaluate the impact of the nanofluids on pressure drop and heat transfer characteristics in the micro-cylinder groups. The study results demonstrate that, for all the nanofluids studied, the pressure drop and friction factor of the micro-cylinder groups increased with increasing Reynolds number. This behavior can be attributed to the interaction between the nanoparticles and the wall, which results in an increase in friction. Furthermore, the Nusselt number was found to increase with increasing Reynolds number. The SiC/Water nanofluid exhibited the highest Nusselt numbers among the four nanofluids tested, indicating that it provides better heat transfer performance than the other nanofluids. These results are consistent with experimental findings, indicating that the numerical simulations were accurate and reliable.